Efektivitas Penerapan Model Pembelajaran Advance Organizer berbasis Peta Konsep untuk Mata Kuliah Qawaid terhadap Daya Ingat Mahasiswa - Rohayati, Enok (Tapis: Jurnal Penelitian Ilmiah, 2018)
This study aimed to improve the memory of students of the Arabic Language Education Study Program at the Faculty of Education and Teacher Training in State Islamic University of Raden Fatah Palembang through Advance Organizer Learning Models based on concept maps. This experimental research employed 40 students consist of experimental and control class. According to Pre-survey data showed that students' average memory in the experimental class reached 4.59%, while the control class reached 4.45%. The target of this study was to improve the students’ memory until 81%. Data collection techniques was employed using action tests were then analyzed quantitatively. After being given a treatment using the Advance Organizer Learning Model based on Concept Maps, the memory of students in the experimental class was obtained 8.05%. Thus, it can be concluded that Advance Organizer Learning Model based on concept maps can improve student memory in Qowaid courses.